Clinical and histopathological characteristics associated with patients with triple-negative Breast cancer at a national reference hospital, 2012 - 2018: Características clínicas e histopatológicas asociadas a pacientes con Cáncer de Mama Triple Negativo en un Hospital de Referencia peruano, 2012- 2018 - Mandujano-Guizado, Giuliana (2019)
Objective: To determine the clinical and histopathological characteristics associated to patients with triple negative breast cancer of the Hipolito Unanue National Hospital between June 2012 to June 2018. Methods: Cross-sectional analytical study. Results: 134 patients were included, out of which 36 (26.9%) were TN and 98 No TN. Of the histopathological characteristics, the most frequent CD was III and II for the two groups. The histological type that predominated was the infiltrating ductal type in both groups. The high histological grade was characteristic in NT (58%) unlike non TN. The NTs were larger 5.75 cm in contrast to the TNs with 3 cm, and the Ki 67 was higher in the TN 35% in contrast to the NON TN with 15%. In the bivariate analysis the size (RP: 1.4, CI: 1.17-1.68, p = 0.0001), Ki 67 (RP: 1.05, CI: 1.03-1.07, p = 0.001), BMI ≥25 kg/m2 ( RP: 1.14, CI: 1.23-6.22, p = 0.014), Histological Grade 3 (RP: 3.87, CI: 1.74-8.63, p = 0.001), size ≥5 cm (RP: 2.94, CI: 1.33-6.48, p = 0.008) were significant. In the multivariate analysis it was found that grade 3 (PR: 1.74, CI: 1.01-3, p = 0.0046) and Ki 67 (RP: 1.02, CI: 1.01-1.03, p = 0.0001) were histopathological characteristics associated with CMTN. Conclusion: There are histopathological characteristics associated with triple negative breast cancer particularly high histological grade and Ki67 value.